Introduction: An Overview of Loon Research and Conservation in North America. - Paruk, James D.; Mager, John N.; Evers, David C., 1962- (Tufts University. Tisch Library., 2019)
A workshop titled The Status of Gavia: Conservation in Black and White was held at the 5th North American Ornithological Conference on 14 August 2012, in Vancouver, British Columbia. The last such North American meeting focused on loons was at the American Ornithologist's Union meetings in Minneapolis in 1997. During the interim 15 years, our knowledge of this group of diving birds in North America has increased significantly. From the 2012 workshop, as well as from contributions of authors unable to attend, 15 papers are presented in this special issue under five broad headings: behavior, life history and population ecology, movements and migration, habitat and landscape requirements and contaminants. Some highlights include the first data on sex ratios in Common Loon (Gavia immer) chicks, the first adult survival estimates for Red-throated Loons (G. stellata), and first reports of mercury exposure in Yellow-billed Loons (G. adamsii) from Alaska and Canada. In addition, a new long-distance migration record for the Common Loon, a landscape assessment of Common Loons in Massachusetts, and oil concentrations in loons wintering in Barataria Bay, Louisiana (one of the areas hit hardest by the Deepwater Horizon Oil Spill) are documented. We hope this collection of papers will be useful to researchers and wildlife managers in North America and abroad.